PERJUANGAN PENETAPAN BATAS WILAYAH PERAIRAN LAUT DI INDONESIA - Suparlan Suparlan (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2011)
Abstract: Territory is an important element of a country. After the development of the territorial countries foundation, i.e. countries struggling for their boundaries explicitly, countries has tried to put some basis that can be accepted by all parties. Indonesia is a very broad archipelagic state consisting of thousands of islands joined by waters. The position of this country makes it have explicit and clear regulations. The government has struggled by many ways in order to unite thearchipelagic Indonesia. Therefore, Indonesia will not be harmed by other countries. The existing regulations are also hoped harmless for others. Archipelagic conceptions as territorial conceptions in the firther development prove to be the conceptions of institutional politics with wide dimension. It seizes not only geographical physical aspects, but also political, economic, socio-cultural, peacefulness, and forhess aspects. The success ofstruggling in creating archipelagic conceptions thesedays can be categorized asjuridical success. However, it can be a foundation for the development of this country in the future.